Assembly and analysis of the first complete mitochondrial genome sequencing of main Tea-oil Camellia cultivars Camellia drupifera (Theaceae): revealed a multi-branch mitochondrial conformation for Camellia - Heng Liang; Huasha Qi; Jiali Chen; Yidan Wang; Moyang Liu; Xiuxiu Sun; Chunmei Wang; Tengfei Xia; Xuejie Feng; Shiling Feng; Cheng Chen; Daojun Zheng (BMC Plant Biology)
Abstract Background Tea-oil Camellia within the genus Camellia is renowned for its premium Camellia oil, often described as “Oriental olive oil”. So far, only one partial mitochondrial genomes of Tea-oil Camellia have been published (no main Tea-oil Camellia cultivars), and comparative mitochondrial genomic studies of Camellia remain limited. Results In this study, we first reconstructed the entire mitochondrial genome of C. drupifera to gain insights into its genetic structure and evolutionary history. Through our analysis, we observed a characteristic multi-branched configuration in the mitochondrial genomes of C. drupifera. A thorough examination of the protein-coding regions (PCGs) across Camellia species identified gene losses that occurred during their evolution. Notably, repeat sequences showed a weak correlation between the abundance of simple sequence repeats (SSRs) and genome size of Camellia. Additionally, despite of the considerable variations in the sizes of Camellia mitochondrial genomes, there was little diversity in GC content and gene composition. The phylogenetic tree derived from mitochondrial data was inconsistent with that generated from chloroplast data. Conclusions In conclusion, our study provides valuable insights into the molecular characteristics and evolutionary mechanisms of multi-branch mitochondrial structures in Camellia. The high-resolution mitogenome of C. drupifera enhances our understanding of multi-branch mitogenomes and lays a solid groundwork for future advancements in genomic improvement and germplasm innovation within Tea-oil Camellia.